2007
DOI: 10.1021/bm070212p
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Peroxidase-Catalyzed Synthesis of Chiral Polyaniline

Abstract: Micellar peroxidase-catalyzed synthesis of chiral polyaniline (PANI) in the presence of dodecylbenzenesulfonic acid (DBSA) was developed. The effect of DBSA concentration on the catalytic efficiency of horseradish and palm tree peroxidases was examined. Favorable conditions for the enzymatic synthesis of chiral PANI, determined by a multiple factors design, demonstrated that the PANIs with the highest chirality were produced in the presence of low concentrations of optically active camphorsulphonic acid (CSA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…It was recently claimed that chiral, conducting, and water-dispersible PANI was prepared by the HRP/H 2 O 2 -triggered polymerization of aniline in AOT micellar solution without any other chiral inducer but HRP itself (Zou et al 2013). Micelles from dodecylbenzenesulfonate in the presence as well as the absence of optically active CSA were also used as templates for the formation of chiral conducting PANI with PTP/H 2 O 2 at pH 3.5 (Caramyshev et al 2007). The SDBS micelle-assisted laccase-catalyzed oxidative polymerization of aniline with O 2 at pH 3.5–4.0, leading to stable dispersions of PANI, was reported by Streltsov et al (2008, 2009) and Zhang et al (2014b).…”
Section: Enzymatic Polymerization Of Arylaminesmentioning
confidence: 99%
“…It was recently claimed that chiral, conducting, and water-dispersible PANI was prepared by the HRP/H 2 O 2 -triggered polymerization of aniline in AOT micellar solution without any other chiral inducer but HRP itself (Zou et al 2013). Micelles from dodecylbenzenesulfonate in the presence as well as the absence of optically active CSA were also used as templates for the formation of chiral conducting PANI with PTP/H 2 O 2 at pH 3.5 (Caramyshev et al 2007). The SDBS micelle-assisted laccase-catalyzed oxidative polymerization of aniline with O 2 at pH 3.5–4.0, leading to stable dispersions of PANI, was reported by Streltsov et al (2008, 2009) and Zhang et al (2014b).…”
Section: Enzymatic Polymerization Of Arylaminesmentioning
confidence: 99%
“…For example, proteins can be incorporated into conducting polymers whilst retaining their biological integrity . Aboutanos et al ( 1999) reported the preparation of chiral polyaniline-camphorsulfonic acid colloids using silica as the dispersant in the absence of a steric stabiliser, whereas Caramyshev et al ( 2007) proposed the micelar synthesis of chiral conducting polyaniline in presence de dodecylbenzenesulfonic acid using an enzyme as a catalyst for aniline polymerization. Okuno et al (2002) also proposed a polypyrrole colloid that had been prepared electrochemically and overoxidized at +1.5 V to create a complementary cavity for recognition of molecules structurally similar to the dopant.…”
Section: Enantioselective Electrochemical Sensorsmentioning
confidence: 99%
“…DBSA has also been used along with a laccase derived from the fungi Trametes hirsute to produce conducting PANI (46,47). Additionally, a chiral PANI was produced with palm tree peroxidase (PTP), DBSA, and low concentrations of CSA (48). PTP was shown to have a higher enzymatic activity compared to HRP both with and without the presence of DBSA.…”
Section: Micellar-based Templatementioning
confidence: 99%